Impact of Prey Harvesting on the Stability of a Three-Species Food Chain Model with a Generalist Predator - S. Ganga; S. Vijaya (Utilitas Mathematica, 2025)
In this study, which involves a prey, an intermediate specialist predator, and a top predator exhibiting generalist behavior, we examine the stability of a three-species food chain model. Harvesting is applied to the prey. The primary objective is to investigate how varying the harvesting rate influences the stability of the system, particularly the coexistence of all three species. We analyze the positivity, boundedness, equilibrium points, and stability of the model, and employ numerical simulations to support the theoretical analysis and explore how different harvesting intensities affect species persistence.